Paradigma Pendidikan Islam dalam Teori Belajar: Analisis Brhavioristik, Kognitif, Humanistik, dan Konstruktivistik - Malida Nur Izzatul Mursyidah; Mu'alimin Mu'alimin; Mukaffan Mukaffan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The paradigm of Islamic education requires the integration of Western learning theories with an Islamic perspective to create a holistic approach to education. With the rapid development of psychological theories in education, such as behaviorism, cognition, humanism, and constructivism, it is essential to examine their relevance within the context of Islamic education. This article aims to analyze the integration of these theories in Islamic learning, with a focus on their connection to key Islamic concepts such as reward-punishment (pahala-dosa), reflection (tafakkur), self-actualization, mutual assistance (ta'awun), and consultation (syura). This study uses a literature review method with a qualitative approach. Articles were gathered through Google Scholar and Publish or Perish with keywords